Meningkatkan Prestasi Belajar Siswa Sekolah Dasar Dengan Menggunakan Media Gambar Pada Materi Wudhu - Raudah Lestari (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to improve students’ learning achievement on the topic of wudhu through the use of picture media at SD Al-Washliyah No. 83 Gunting Saga. This research is a Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of the stages of planning, action, observation, and reflection. The subjects of the study were 25 students. Data collection techniques were carried out through learning achievement tests and observation of students’ learning activities during the instructional process. The results of the study show an improvement in students’ learning achievement after the implementation of picture media in teaching the wudhu topic. In the pre-cycle stage, out of 25 students, 10 students (40%) achieved mastery learning, while 15 students (60%) had not yet achieved mastery. After the implementation of actions in Cycle I, the number of students achieving mastery increased to 17 students (68%), while 8 students (32%) had not yet reached the Minimum Mastery Criteria (KKM). Furthermore, in Cycle II, there was a significant improvement, where 23 students (92%) achieved mastery learning and only 2 students (8%) had not yet mastered the material. It can be concluded that the use of picture media is effective in improving students’ learning achievement on the topic of wudhu. Picture media helps students understand the steps of wudhu in a more concrete, engaging, and easily comprehensible way.